Chemical Composition of Rice and Analytic Hierarchy Process Technique in Preference of Consumer Rice Buying - GAYTANCIOGLU, OKAN; LORCU, FATMA; AFACAN, AYSE (Asian Journal of Chemistry, 2010)
In this research, an evaluation is made for three types of rice by using analytic hierarchy process technique. According to criteria determined by 600 consumers and specialist the decision is made on the most appropriate rice types. In the experiement, moisture content and crude protein content of the seed samples were analyzed. Total ash content was determined according to ISO method. Lipid extraction from the seed samples was carried out and chemical composition of rice was determined.